1997
DOI: 10.1046/j.1365-2567.1997.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Recipient age determines the success of intraperitoneal transplantation of peritoneal cavity B cells

Abstract: In vivo studies of lymphocyte biology have used intravenous (i.v.) injection as the primary mode of cell transfer, a protocol consistent with the anatomic distribution of most lymphocytes. However, for study of peritoneal cavity B cells, i.v. injection does not correlate with anatomical localization. This report describes the restoration of B‐cell function in B lymphocyte‐defective X‐chromosome‐linked immune‐defective (XID) mice after intraperitoneal transfer of immunoglobulin heavy chain (Igh)‐disparate perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…was postulated that migration from the PerC to the systemic circulation is necessary for B cells to produce Ab. Evidence for this hypothesis was the presence of transferred donor PerC-derived Ab-secreting cells in the SPL of host B lymphocyte-defective Xchromosome-linked immune-defective mice (38). This hypothesis is consistent with our data, and would suggest a model wherein PerC B-1b cells expand locally and migrate to the SPL, where they become Ab-producing cells.…”
Section: Discussionsupporting
confidence: 89%
“…was postulated that migration from the PerC to the systemic circulation is necessary for B cells to produce Ab. Evidence for this hypothesis was the presence of transferred donor PerC-derived Ab-secreting cells in the SPL of host B lymphocyte-defective Xchromosome-linked immune-defective mice (38). This hypothesis is consistent with our data, and would suggest a model wherein PerC B-1b cells expand locally and migrate to the SPL, where they become Ab-producing cells.…”
Section: Discussionsupporting
confidence: 89%
“…It was previously shown that transplant of B-1 B cells to peritoneal cavities of XID mice did not result in IgM production in XID mice greater than 8 weeks of age (41), but intravenous transfer did restore IgM serum levels in 8- to 12-week-old mice (30, 41). Although XID mice in our studies were between 6 and 8 weeks old at the time of B-1 B cell transfer and the numbers of PerC B-1 B cells were restored (Fig.…”
Section: Resultsmentioning
confidence: 99%